Optimasi Pola Taman Daerah Irigai Uwai Pangoan Kabupaten Kampar - Tria, Lukis; Siswanto, Siswanto; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Uwai Pangoan irrigation area is located in Kampar district which one of the rice-producing district in Riau province. The potential area of Muara Jalai irrigation area is 800 Ha, but it is functional area is just 615 Ha. Processing of agricultural land of this irrigation area was done twice in a year with Padi-Bera-Bera cropping pattern. The functional area is still small and the cropping pattern in such a way, this suggests that the potential of water resources and land owned by the irrigation area is not utilized optimally. Based on the condition, optimization study carried out to maximize the profits of farming results, based on the optimal planting area using a linear program. The mainstay volume and crop water requirements of each alternative cropping pattern planned are used as restrictions/constrains as input for operation of linear program. The results of these calculations are expected to know the optimal planting area according to the cropping pattern and cropping season, also the greatest profits to be obtioned. The results of several planned alternative cropping pattern was obtained which get the greatest profits is Padi/Kacang Hijau – Padi/Kacang Hijau – Kacang Hijau cropping pattern. The cropping pattern is scheduled for early planting December period I with the profits is Rp 5.711.999.000 and 300% cropping intensity.Key words: mainstay volume, irrigation water requirements, cropping pattern, optimation, linear program